2010
DOI: 10.1002/j.0022-0337.2010.74.10.tb04971.x
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone Hygiene: Potential Risks Posed by Use in the Clinics of an Indian Dental School

Abstract: The objectives of this cross-sectional study were to determine the level and type of bacterial contamination of the mobile phones of dental personnel involved in direct patient care and to determine the usefulness of cleaning with 70 percent isopropyl alcohol for decontamination. Dental faculty and trainees in an Indian dental school were asked to participate in a study in which a questionnaire concerning patterns of mobile phone use and disinfection was administered. Swabs from mobile phones of the participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 17 publications
4
40
0
Order By: Relevance
“…However, mobile phones are usually touched during or after the examination of patients without hand washing, but not cleaned and can harbor various pathogens and become a potential source of hospital associated infections among patients and even medical staff [7]. Mobile phones harbor pathogens microorganism, and high temperature cause increasing the amount of microorganisms.…”
mentioning
confidence: 99%
“…However, mobile phones are usually touched during or after the examination of patients without hand washing, but not cleaned and can harbor various pathogens and become a potential source of hospital associated infections among patients and even medical staff [7]. Mobile phones harbor pathogens microorganism, and high temperature cause increasing the amount of microorganisms.…”
mentioning
confidence: 99%
“…Kilic et al 15 found that only 33% of mobile phones that were cleaned at least once a week with alcohol were contaminated, albeit solely with S.epidermidis. While Jayalakshmi et al 16 established that 70% isopropyl alcohol disinfected nearly all mobile phones in their study, with a gross reduction in the number of organisms, Ramesh et al 17 , found that it was the act of daily cleaning, not the cleaning method used (alcohol versus dry cloth) that was significantly associated with amount of growth, corroborated by Singh et al 18 . This questions the efficiency of alcohol as a cleaning agent for mobile phones and indicates that further investigation is needed into the optimal disinfection method for these devices.…”
Section: Resultsmentioning
confidence: 82%
“…Pathogen transmission and their long-lasting survival impose the implementation of strategies that indicate mandatory regular disinfection procedures of everyday household items. Preventive measures, including the use of alcoholbased disinfectants or bactericidal substances with nanosilver compounds in disinfection of different surfaces, are recommended by a number of authors (Singh et al, 1998(Singh et al, , 2010Ulger et al, 2009). Pulit et al (2011) describe the nanosilver as a highly effective antimicrobial and anti-fungal agent, used for creating aseptic conditions.…”
Section: Experimental Groupmentioning
confidence: 99%
“…The mobiles can be also effectively disinfected with 70% isopropyl alcohol-based means or wipes saturated in the solution of 0.5% chlorhexidine and 70% isopropyl alcohol (Brady et al, 2009). Singh et al (2010) conducted a telephone disinfection using disin-fecting wipes moistened with 70% isopropyl alcohol. The authors obtained a reduction of bacteria on phones by 87%.…”
Section: Experimental Groupmentioning
confidence: 99%
See 1 more Smart Citation